Right-Angled Traction Bronchiectasis in Differentiating Idiopathic Pulmonary Fibrosis Without Honeycombing From Idiopathic Nonspecific Interstitial Pneumonia. Issue 6 (June 2020) - Kim, Heekyung; Yoon, Soon Ho; Lee, Hyun-Ju; Song, Seung Geun; Koh, Jaemoon; Jeon, Yoon Kyung; Chae, Kum Ju; Jin, Gong Yong; Jin, Kwang Nam; Lee, Ki Yeol; Goo, Jin Mo
Abstract : Objectives: The aim of this study was to conduct a radiopathologic evaluation of right-angled traction bronchiectasis to differentiate idiopathic pulmonary fibrosis (IPF) without honeycombing from idiopathic nonspecific interstitial pneumonia (NSIP). Materials and Methods: The derivation cohort included 78 consecutive patients with idiopathic NSIP (n = 39) or IPF (n = 39) without honeycombing who underwent preoperative thin-section computed tomography scans at a single tertiary hospital. The validation cohort comprised 22 patients (14 IPF and 8 NSIP) from another institution. We assessed conventional computed tomography findings, right-angled traction bronchiectasis on minimum intensity projection (MinIP) images, and pathologic features associated with right-angled bronchiectasis. Right-angled traction bronchiectasis was defined as abrupt kinking of a single bronchus by over 90 degrees or an abrupt angle close to 180 degrees of branching bronchi in the background of fibrosis. In the validation cohort, we evaluated the proportion of correct IPF diagnoses and interobserver agreement of 4 radiologists before and after reviewing MinIP images. Results: A probable usual interstitial pneumonia (UIP) pattern (odds ratio [OR], 6.948; 95% confidence interval [CI], 1.525–31.654; P = 0.012) and right-angled traction bronchiectasis (OR, 6.004; 95% CI, 1.980–18.209; P = 0.002) were independently associated with IPF. Patients with right-angled traction bronchiectasis were more likely to have extensive reticular opacity (OR, 1.149; 95% CI, 1.077–1.225; P < 0.001) and pathologically were more likely to have a broad extent of subpleural fibrosis (OR, 4.000; 95% CI, 1.457–10.987; P = 0.007) and relatively thick fibrosis (OR, 7.750; 95% CI, 2.504–23.991; P < 0.001). After reviewing MinIP images, the proportion of correct diagnoses increased from 40.9% to 54.5% to 50.0% to 77.3%. The mean kappa value for right-angled traction bronchiectasis was 0.489 ± 0.192. Conclusions: Right-angled traction bronchiectasis pathologically reflected a subpleural predominance of fibrosis and partly supported the radiologic differentiation of IPF without honeycombing from idiopathic NSIP. Abstract : Supplemental digital content is available in the text.